Performance and Key Factors of Cloud Computing Implementation in the Public Sector - Hasimi Sallehudin; Azana Hafizah Mohd Aman; Razli Che Razak; Mohammad Ismail; Nur Azaliah Abu Bakar; Ahmad Firdause Md Fadzil; Rogis Baker (International Journal of Business and Society, 2020)
The reason to explain the cloud computing assimilation, as well as the understanding of the operational performance, still remains unclear. To investigate this issue, this study has examined the assimilation of cloud computing by examining the organization’s implementation of cloud computing and performance in the Malaysian public sector. Grounded by the Diffusion of Innovation Theory (DOI), Technology-Organization-Environment Framework (TOE) and IS Success Model. This study proposes a framework by decomposing Technological characteristic, Organizational characteristics, Environmental characteristics and Human characteristics as factors. A total of 169 agencies from the Malaysian public sector have participated in this study. Data for all the study variables have been collected through self-administered survey questionnaires and analysed using SEM-PLS. The study has shown that the effect of the operational effectiveness of cloud implementation is at a lower level. The study also reveals that factors of relative advantage, compatibility, perceived risks, top management support, and organizational readiness are found to have a significant effect on cloud computing implementation. However, both external support and government regulations are not significant to the cloud computing implementation in the Malaysian public sector. The results indicate that the model provides a good understanding of the factors that influence the implementation of cloud computing as well as operational performance.